THE PROMINENT HISTORIOGRAPHY AS STRENGTHENING THE SCHOOLS OF FIQH AND SUFISM - Thohir, Ajid (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2012)
The study of historiography has a great contribution to understand the dynamics of lslamic society in the past both cultural and intellectual. The emergence trend of the persona themes and how many works are coming up that should be conceived as an ideological character which places the important position of figure in the Islamic history. The relationship between a work and the cultural dynamics at any time and space reflects their respective historical work which is highly motivated by the cultural interest complexity. The study of persona in the lslamic historiography occupies a strategic position, particularly in strengthening and forming the schools. in the Islamic world, especially in the field of fiqh and Sufism. The study of biographical persona is not only restricted to thabaqat, tarjamah, and ansâb, but also to the study of persona that leads to the formation of hagiography (Manaqib), putting someone as a top figure of both intellectual and spiritual in the religious world. The Manaqib Book is a symbol in the schools tie and forms a psychological cohesiveness for the disciples of madzhab.